Hospital care does not meet the communication needs of patients with hearing loss: A qualitative study of patient experiences - Alex DeBusschere; Meaghan Lunney; Sonja Reid; Nancy Verdin; Shannan Love; Stephanie Thompson; David Nicholas; Tiffany Boulton; Kara Schick-Makaroff; Lorienne Jenstad; Sharon Straus; Jayna Holroyd-Leduc; et al. (PLoS ONE, 2025)
Background Good communication is essential for high quality healthcare. People with hearing loss face communication challenges during health encounters, which may compromise their experience with care and outcomes, especially in noisy or stressful acute care facilities. Tools and strategies to facilitate two-way communication with these patients and other members of their healthcare team may help address this gap. This study describes the communication-related experiences of patients with hearing loss in Alberta hospitals, which can help inform future strategies in this setting. Methods Drawing on qualitative description, we conducted focus groups and individual interviews with people with hearing loss who had a recent hospital experience in Alberta, Canada. Focus group and interview transcripts were abductively coded and analyzed, guided by established communication frameworks to explore experiences and opportunities for change. Results Fourteen people participated in 3 focus groups and 3 interviews. Overall, participants perceived hospitals as not meeting their communication needs. We identified 3 themes: 1) Hearing loss is an invisible disability; 2) Communication is a team effort; 3) Every patient has different needs in different situations. Conclusions Patients with hearing loss experience communication gaps while in hospital, possibly related to the invisibility and stigma of hearing loss, the lack of awareness about how to identify and accommodate different communication needs, and systemic barriers. Strategies to identify patients’ communication needs, train healthcare providers, and increase the uptake of communication tools may help improve communication in this population.